Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter P - Section P.4 - Polynomials - Exercise Set - Page 56: 55



Work Step by Step

RECALL: $(a-b)^3=a^3-3a^2b+ 3ab^2-b^3$ Use the formula above with $a=x$ and $b=3$ to obtain: $=x^3-3(x)^2(3)+3(x)(3^2)-3^3 \\=x^3-9x^2+3x(9)-27 \\=x^3-9x^2+27x-27$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.